2016
DOI: 10.14260/jemds/2016/215
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Clinical Study to Evaluate the Efficacy of Levobupivacaine With Clonidine and Levobupivacaine With Dexmedetomidine in Supraclavicular Brachial Plexus Block

Abstract: The objective of this study is to compare clonidine and dexmedetomidine as an adjuvant to levobupivacaine in supraclavicular brachial plexus block with respect to onset, duration of sensory and motor block and duration of analgesia. MATERIALS AND METHODS A total of 90 ASA grade I and II patients of either sex, aged 18-60 yrs. scheduled for elective upper limb surgeries under supraclavicular brachial plexus block were divided into 3 equal groups in a randomized fashion. Group L (n=30) received 1 mL NS, group LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Across all included studies, a total of 3332 patients were assessed. DEX was used as an adjuvant to several different local anesthetics, which included ropivacaine [ 23 , 34 , 39 , 41 , 42 , 45 47 , 49 , 50 , 52 , 56 , 57 , 59 , 63 66 , 68 , 72 – 74 , 76 , 78 , 80 , 81 , 84 , 85 ], bupivacaine [ 20 , 35 , 37 , 38 , 40 , 51 , 53 55 , 67 , 69 , 71 ], levobupivacaine [ 21 , 43 , 44 , 48 , 60 62 , 79 , 83 ], and lidocaine [ 22 , 36 , 70 , 77 , 86 ]. Across the studies, the dose of DEX ranged from 0.5 μg/kg to a total of 150 μg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all included studies, a total of 3332 patients were assessed. DEX was used as an adjuvant to several different local anesthetics, which included ropivacaine [ 23 , 34 , 39 , 41 , 42 , 45 47 , 49 , 50 , 52 , 56 , 57 , 59 , 63 66 , 68 , 72 – 74 , 76 , 78 , 80 , 81 , 84 , 85 ], bupivacaine [ 20 , 35 , 37 , 38 , 40 , 51 , 53 55 , 67 , 69 , 71 ], levobupivacaine [ 21 , 43 , 44 , 48 , 60 62 , 79 , 83 ], and lidocaine [ 22 , 36 , 70 , 77 , 86 ]. Across the studies, the dose of DEX ranged from 0.5 μg/kg to a total of 150 μg.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of bradycardia and hypotension was described in 28 studies [ 23 , 34 37 , 39 – 42 , 45 , 47 , 48 , 51 – 53 , 58 , 61 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 83 – 85 ] and 26 studies [ 23 , 34 – 36 , 39 – 42 , 45 48 , 51 – 53 , 58 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 84 , 85 ] respectively. Pooled analysis showed that perineural DEX>60 μg increased the risk of bradycardia (risk difference [RD]: 0.16, 95% CI: 0.06 to 0.26, I 2 = 97%, P = 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, pairwise meta‐analysis of 53 trials for sensory block duration [73–111, 113–122, 125, 126, 128, 129] and 53 trials for motor block duration [73–111, 113–122, 125, 126, 128, 129] comparing perineural dexmedetomidine vs. control arms did not reveal any sub‐group differences by indexing status (see online Supporting Information). Consequently, indexed and non‐indexed papers were pooled and analysed in the network, as decided a priori.…”
Section: Resultsmentioning
confidence: 99%
“…45,[63][64][65]78,80 Nineteen trials compared dexmedetomidine with clonidine in 1130 patients. 31,42,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] Different doses of adjuvants were compared in seven trials. 17,22,30,40,62,64,86 One trial tested clonidine with different local anaesthetics 25 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The duration of BPB was 205 min (TSA adj. 95% CI 162, 249; p < .00001; 1030 patients; 19 trials) 31,42,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] longer for dexmedetomidine compared with clonidine (weighted mean duration in clonidine group 481 min) (Figure 4, Appendix S7 and Table 2).…”
Section: Dexmedetomidine Versus Clonidinementioning
confidence: 99%